Making matters a vocabulary for collective arts - Wesseling, Janneke 1955-; Cramer, Florian 1969- (Valiz, 2022)
The concern for material existence on our planet is more pressing than ever. ‘Making Matters’ spells out various roles that visual artists and designers play when facing these issues. Collective action is necessary and inevitable. Collective action often changes the artist’s identity and ways of working, from individuality and autonomy to collectivity and collaboration, both locally and globally. This books gives insight into practices that are taking place at the moment on all continents. These practices do not conform to a Western concept of art, nor to traditional distinctions between art, design, research, and activism.
Keywords: Kollektiv; Künstler; Klimaänderung; Globalisierung; Kunst; Umweltschaden; Art / Terminology; Design / Terminology; Artistic collaboration / Terminology; Aufsatzsammlung